Factors Influencing Teachers’ Readiness In Implementing The Independent Curriculum in Indonesia - Rianti, Andini; Sujarwo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The low readiness of teachers in implementing the Independent Curriculum is a challenge in achieving educational transformation. Several internal and external factors are believed to influence this readiness, but they have not been widely studied in an integrated manner. This study aims to analyze in depth the influence of principal leadership, teacher professionalism, and training experience on teacher readiness in implementing the Independent Curriculum. This study uses a quantitative approach with an ex post facto design. The study population consisted of 174 teachers, and the sample comprised 121 teachers selected using the Yamane formula and the Proportional Random Sampling technique. Data were collected through a Likert scale questionnaire that had been tested for validity and reliability. Data analysis techniques included descriptive analysis, classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity), as well as multiple linear regression analysis, t-test, and F-test. The study's results showed that principal leadership, teacher professionalism, and training experience had a significant influence, both partially and simultaneously, on teacher readiness. This study concludes that these three variables are important factors in enhancing teacher readiness in response to curriculum changes. The implications of these findings underscore the importance of education policy in strengthening principal leadership, enhancing professionalism, and providing relevant and sustainable training for teachers.